2017
DOI: 10.1038/nm.4295
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the hepatokine selenoprotein P increases responsiveness to exercise in mice through upregulation of reactive oxygen species and AMP-activated protein kinase in muscle

Abstract: Exercise has numerous health-promoting effects in humans; however, individual responsiveness to exercise with regard to endurance or metabolic health differs markedly. This 'exercise resistance' is considered to be congenital, with no evident acquired causative factors. Here we show that the anti-oxidative hepatokine selenoprotein P (SeP) causes exercise resistance through its muscle receptor low-density lipoprotein receptor-related protein 1 (LRP1). SeP-deficient mice showed a 'super-endurance' phenotype afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 57 publications
2
129
2
1
Order By: Relevance
“…AX is a strong antioxidant and could scavenge physiological reactive oxygen species (ROS) generated during exercise training, thereby canceling the beneficial effects of exercise with regard to endurance and glucose tolerance. Previous reports have also suggested that an exercise tolerance test is important to assess the metabolic adaptations in muscle and exercise‐induced ROS generation have beneficial effect on metabolic adaptation in muscle . Thus, we next examined whether AX affected the training‐induced increase in exercise tolerance.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…AX is a strong antioxidant and could scavenge physiological reactive oxygen species (ROS) generated during exercise training, thereby canceling the beneficial effects of exercise with regard to endurance and glucose tolerance. Previous reports have also suggested that an exercise tolerance test is important to assess the metabolic adaptations in muscle and exercise‐induced ROS generation have beneficial effect on metabolic adaptation in muscle . Thus, we next examined whether AX affected the training‐induced increase in exercise tolerance.…”
Section: Resultsmentioning
confidence: 98%
“…It is possible that AX somehow sequesters ROS that cause damage, but not the ROS that induce beneficial effects. Previous reports suggested that exercise‐induced generation of ROS not only causes oxidative damage, but that the ROS also function as signaling molecules to facilitate beneficial molecular adaptations . To rule out the possibility that AX might mitigate the ROS‐mediated positive effects of exercise training by activating several molecules, including AMPK and PGC‐1α, in the muscle, we examined whether AX had any effect on H 2 O 2 ‐induced AMPK phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activated AMPK stimulates PGC1 α gene expression in response to endurance exercise (Misu et al. ). It is still unclear whether activation and interaction of these signal transductions are distinct between slow‐ and fast‐ twitch fibers upon denervation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, AMP-activated protein kinase (AMPK) enhances FoxO3 transcriptional activity when FoxO3 is translocated into nucleus (Greer et al 2007), whereas peroxisome-proliferator-activated receptor-c coactivator-1 alpha (PGC1a) inhibits FoxO3 function (Sandri et al 2006). Interestingly, activated AMPK stimulates PGC1a gene expression in response to endurance exercise (Misu et al 2017). It is still unclear whether activation and interaction of these signal transductions are distinct between slow-and fast-twitch fibers upon denervation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that SeP serves as a hepatokine, promoting glucose intolerance and insulin resistance in type 2 diabetes. 5) SeP is upregulated in the liver of type 2 diabetes patients, and high levels of SeP impair insulin signaling and glucose metabolism in both liver and muscle of mice. 5) We have recently reported that SeP is involved in exercise resistance by suppressing the levels of exercise-induced reactive oxygen species (ROS) in skeletal muscle.…”
mentioning
confidence: 99%